Strengthening the Character of 21st-Century Educators: A Philosophical Analysis of the Ministry of Education and Culture's Teacher Psychological Welfare Program - Putra Asga Elevri; Yadi Ruyadi; Encep Syarief Nurdin; Asep Dahliyana; Bunyamin Maftuh; Mupid Hidayat; Momod Abdul Somad; Warlim Isya (Journal of Pedagogy and Education Science, 2026)
Twenty-first-century education requires teachers to function not only as knowledge transmitters but also as moral agents who cultivate values, character, and meaningful learning experiences. Yet increasing administrative demands, policy changes, professional dilemmas, and emotional exhaustion often weaken teachers’ psychological well-being and their ability to serve as authentic role models. This study examines how the Teacher Psychological Well-Being Program, comprising the Technical Guidance Program and the Teacher Psychological Well-Being Survey developed by Indonesia’s Ministry of Primary and Secondary Education, strengthens educators’ values and character from a philosophical perspective. Using a qualitative descriptive-analytical case study, the research analyzes official program documents and relevant scholarly literature. Data were examined thematically by mapping program components to Aristotelian eudaimonia, ontological security, Ryff’s psychological well-being framework, and character education through habituation. Findings indicate that the program provides a holistic intervention integrating reflective practices, resilience-building strategies, value habituation, and multidimensional well-being assessment. Through the “My Tree” framework, teachers develop self-acceptance, autonomy, purpose in life, positive relationships, environmental mastery, and personal growth. The program shifts attention from deficit-based stress management toward human flourishing by operationalizing eudaimonia through meaningful professional development and supportive social engagement. Reflective activities and autonomy-enhancing practices also strengthen ontological security by fostering coherent professional identities amid systemic challenges. Positive micro-practices, including gratitude journaling, appreciation circles, grounding techniques, and affirmations, reinforce authentic character formation. The study concludes that philosophically grounded well-being interventions should be integrated into educational policy to support sustainable, human-centered, and high-quality education.